THE EFFECT OF TWO STAY TWO STRAY METHODE AND SPRITUAL INTELLIGENCE TO LEARNING OUTCOMES OF STUDENTS AL-QUR’AN HADITS ON CLASS X MAN BINJAI - Achyar Umayyah Nst, Achyar Zein, Wahyudin Nur Nasution (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2019)
Abstract: The research destination to determine: (1) The effect of learning methods of Two StayingTwo Stray on the learning outcomes of Al-Qur’an Hadith students at MAN Binjai. The influence ofexpository learning methods on learning outcomes of Al-Qur’an’s Hadith students at MAN Binjai. (2)For students who have high spiritual intelligence, there are learning outcomes of the Al-Qur’an Hadithstudents who learn by the method of staying two stray with the expository method. (3) For studentswho have low spiritual intelligence, there is the learning result of the Al-Qur’an Hadith students wholearn by the method of staying two stray with the expository method. (4) Whether or not there is aninteraction between the learning method and spiritual intelligence with the learning outcomes of Al-Qur’an’s Hadith students at MAN Binjai.Key Word: Spritual Intelligence, Learning, and Student